2015
DOI: 10.1007/s11747-015-0452-7
|View full text |Cite
|
Sign up to set email alerts
|

A brand built on sand: Is acquiring a local brand in an emerging market an ill-advised strategy for foreign companies?

Abstract: The literature that focuses on acquisitions from the consumer perspective has generally neglected the brand strategy of cross-border acquisitions in an emerging market by a developed country brand. However, research in this field appears necessary, considering the high failure rate of M&As, the common practice of Western/global companies of augmenting their brand portfolio through local acquisitions, and the sensitivity of emerging market consumers to foreign brands. The present study is an initial attempt to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 125 publications
(185 reference statements)
3
62
0
Order By: Relevance
“…According to this argument, the negative influences of brand globalness on attitudes toward CMSPs are rooted in an antagonism between the global positioning inherent in the foreign global brand (out-group brand) and the local symbolism of culture, heritage, and country embedded in the product (i.e., product local iconness; Özsomer 2012) and cherished by local consumers (in-group). This perceived antagonism among emerging-market consumers has already been noted in the literature in the form of global company animosity or consumer reactance to the acquisition of local brands by global companies (Alden et al 2013; Heinberg, Ozkaya, and Taube 2016). Importantly, because of our focus on CMSPs, we are interested in product local iconness.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 73%
See 1 more Smart Citation
“…According to this argument, the negative influences of brand globalness on attitudes toward CMSPs are rooted in an antagonism between the global positioning inherent in the foreign global brand (out-group brand) and the local symbolism of culture, heritage, and country embedded in the product (i.e., product local iconness; Özsomer 2012) and cherished by local consumers (in-group). This perceived antagonism among emerging-market consumers has already been noted in the literature in the form of global company animosity or consumer reactance to the acquisition of local brands by global companies (Alden et al 2013; Heinberg, Ozkaya, and Taube 2016). Importantly, because of our focus on CMSPs, we are interested in product local iconness.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 73%
“…As such, the mental boundary between out-group and in-group becomes mixed, leading to exclusionary reactions. Recent findings have shown that consumers in emerging markets view brands that are simultaneously global and local iconic as less attractive than those that are either global or local iconic (Heinberg, Ozkaya, and Taube 2016). Other studies on culture mixing have found similar exclusionary reactions (Chiu, Mallorie, and Keh 2009; Torelli et al 2011).…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…In addition, FMCGs are of practical relevance as they combine about a quarter of all advertising spending globally (Nielsen 2013). Moreover, they have the advantage of including numerous brands that consumers are familiar with, many of which are household names (Heinberg et al 2016). As such, there is an extensive pool of brands for our selection process.…”
Section: Empirical Studymentioning
confidence: 99%
“…We restricted the sample to age groups between 18 and 55 years to ensure internet literacy and to avoid the trap of generational differences in emerging markets. Older consumers in emerging markets have enjoyed fewer benefits from economic reforms and often display different shopping behaviors, frequenting wet markets instead of modern shopping formats (Heinberg et al 2016). Overall, we collected 1253 valid respondents in China and 1050 in Japan (approximately 26 per brand), and our samples are representative in terms of gender and respective age groups in each country (Table 2).…”
Section: Empirical Studymentioning
confidence: 99%
“…Therefore, the investments that are necessary to build a global brand may enhance the credibility of a global positioning strategy (Heinberg, Ozkaya, & Taube, 2016;Holt et al, 2004). Accordingly, Özsomer and Altaras (2008) proposed that global brands, "have greater credibility because of greater brand investments and marketing-mix consistency across major markets and time" (page 10, quote by Özomer & Altaras, 2008).…”
Section: Credibility and Attractiveness Of Global And Local Iconic Brmentioning
confidence: 99%